Label-free determination of diffusion coefficients at the nanoscale through modelling of the Surface Plasmon Resonance signal. - Gabriele Antonio Zingale; Irene Pandino; Damiano Calcagno; Maria Luisa Perina; Nunzio Tuccitto; Giuseppe Grasso (PLoS ONE)
Surface plasmon resonance (SPR) is normally used to measure the kinetic parameters of biomolecular interactions between a molecule immobilized on a gold surface and another one flowing in a microfluidic channel above the surface. During the SPR measurements, convection-diffusion phenomena occur inside the microfluidic channels, but they are generally minimized by appropriate experimental setup in order to obtain diffusion free kinetic parameters of the molecular interactions. In this work, for the first time, a commercial SPR apparatus has been used to obtain non canonical scientific parameters. Indeed, a specifically designed SPR experimental setup is described for carrying out measurements of the diffusion coefficient (D) of molecules in solutions. The high precision and reproducibility of the approach, as well as the wide applicability of the newly proposed SPR based method for the measurement of D of many different molecules and biomolecules, are here demonstrated and illustrated in detail.